Management of Patent Ductus Arteriosus in Premature Infants in 2020 - Parkerson, Sarah; Philip, Ranjit; Talati, Ajay; Sathanandam, Shyam (Frontiers in Pediatrics, 2021)
The patent ductus arteriosus (PDA) is the most commonly found cardiac condition in neonates. While there have been several studies and thousands of publications on the topic, the decision to treat the PDA is still strongly debated among cardiologists, surgeons, and neonatologists. This is in part due to the shortage of long-term benefits with the interventions studied. Practice variations still exist within sub-specialties and centers. This article briefly summarizes the history, embryology and histology of the PDA. It also succinctly discusses the hemodynamic significance of a PDA which builds the framework to review all the available literature on PDA closure in premature infants, though not a paradigm shift just yet; it introduces transcatheter PDA closure (TCPC) as a possible armament to the clinician for this age-old problem.